Bericht über meine Kolumbienreise 1952 - Wilhelmy, Herbert (ERDKUNDE, 1953)
In 1952 work in the field was carried out in Colombia by Prof. H. Wilhelmy, D. Phil., of Kiel University. In the Atlantic coastal fringe investigations were made of the pasture and arable areas together with a more detailed study of banana cultivation near Santa Marta. A journey up the Magdalena Valley to its sources presented opportunities of making a great number of interesting observations upon its geomorphology and plant geography. The Cauca Valley too, was a rewarding field for geomorphological investigations in addition to the opportunities it offered for studies of its economic geography, i. e. gold production and the cultivation of sugar cane and cocoa. Climatic conditions during the quarternary ice age and periglacial solifluction were investigated in the Paramos of the East and Central Cordillera, and over all three Cordilleras traverses were made on a number of occasions. During visits to the Pacific coastal zone studies were made of the tropical rain forest, methods of gold production and the beginnings of agricultural development. Somewhat longer sojourns were made for the purpose of studying the economic core regions of Colombia: the coffee zone of Antioquia-Caldas, the tobacco district of Santander and the wheat and potato regions of the cool uplands.